AGREEABLENESS, CONSCIENTIOUSNESS AND SUBJECTIVE WELLBEING - Mayungbo, Olusegun Adedamola (PEOPLE: International Journal of Social Sciences, 2016)
The Big Five Personality factors have long been identified as strong predictors of subjective wellbeing. However, studies on subjective wellbeing have been focused on the affective aspect of personality to the neglect of other dimensions. This study therefore examines the influence of agreeableness and conscientiousness on life satisfaction among residents in Ibadan metropolis. Using a 2-way factorial design and a multistage sampling technique, 10 enumeration areas were selected from each of the five major Local Government Areas (LGAs) in Ibadan metropolis, Oyo State, Nigeria, with simple random technique.Two hundred and twenty households were selected from each of the selected LGAs with the help of enumeration area maps, using systematic technique, making a total of 1,100 households. A questionnaire focusing on socio-demographic profile, life satisfaction scale (r=0.74) and the big 5 personality inventory (r=0.76) was administered to houseowners and renters, who are the participants. Data were analyzed using descriptive statistics and analysis of variance at 0.05 level of significance. Three hypotheses were tested. The result reveals that conscientiousness has a significant main effect on life satisfaction and also interacts with agreeableness to predict life satisfaction F(1,686)=4.15). Emphasis should be on all the Big Five personality factors for a comprehensive examination of personality and life satisfaction.